PERSONALIZATION IN DIGITAL MARKETING: EXPLORING ITS IMPACT ON CONSUMER TRUST AND LOYALTY - Marasabessy, Nabila Cecilia; Hidayat, Muhammad (Penelitian dan Pengembangan Ilmu, 2025)
This research aims to explore how personalization in digital marketing influences consumer trust, focusing on factors that strengthen or weaken that trust. Using a systematic literature review approach with the PRISMA method, we analyzed findings from previous studies related to data-based personalization, transparency, and privacy. The results show that the level of transparency, relevance of content, as well as consumer control over their data play a key role in building trust, while intrusive personalization can undermine it. The practical implications of this research provide guidance for companies in designing ethical and effective digital marketing strategies.